PENGARUH SELF ASSESSMENT SYSTEM TERHADAP KEPATUHAN MEMBAYAR PPN OLEH PENGUSAHA KENA PAJAK DI KOTA LHOKSEUMAWE (Survei pada Bengkel Sepeda Motor di Kota Lhokseumawe) - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2017)
This study on the effect of Self Assessment System to compliance by employers topay PPN taxable in Lhokseumawe. The purpose of this study is to determine theeffect of the Self Assessment System to compliance by employers to pay PPNtaxable in Lhokseumawe. The data used in this study are primary data by dividingquestionnaires to 58 employers taxable motorcycle repair shop in Lhokseumawewere used as samples. The data processing is done with the help of a simple linearequation model SPSS version 16. The results showed that: Self Assessment Systemhave a relationship (correlation) is very strong compliance by employers to pay PPNtaxable in Lhokseumawe. Self Assessment System has ability to explain its influenceto pay PPN compliance by employers taxable in Lhokseumawe. Self AssessmentSystem significantly influence compliance by employers to pay PPN taxable inLhokseumawe.